A new species of large green treefrog (Anura: Hylidae: Litoria) from northern New Guinea - Richards, Stephen J.; Oliver, Paul; Dahl, Chris; Tjaturadi, Burhan (Zootaxa, 2006)
A new species of large green frog of the hylid genus Litoria is described from northern New Guinea. The new species is superficially similar to Litoria graminea and L. infrafrenata. It can be distinguished from L. graminea by the possession of a poorly defined white labial stripe that does not extend beyond the ear, and from L. infrafrenata by the combination of comparatively small adult size (males 57.9–60.4 mm), fully webbed fingers and a call that is a long (0.7–0.9 s) deep guttural growl. It is known from lowland forests around the village of Utai in north-western Papua New Guinea.